The Application of Catalytic Ozonation Technique using UV and Granular Activated Carbon (GAC) for Eliminating in Waste Phenol, COD, and 1,1,2,2-Tetrachloroethane - Ikhsandy, Ferry; Bismo, Setijo; Karamah, Eva Fathul (Universitas Tribhuwana Tunggadewi Malang, 2022)
Process eliminating compounds of phenol, Chemical Oxygen Demand (COD), and 1,1,2,2-tetrachloroethane using catalytic ozonation technique with catalyst Granular Activated Carbon (GAC) combination with Ultra Violet (UV) light emission performed in this study. This study aimed to obtain the effectiveness of applications catalytic ozonation technique using system configuration Ozone/GAC and Ozone/UV/GAC to eliminate waste phenol 1,1,2,2-tetrachloroethane COD with circulation time (0, 15, 30, 45, 60, and 120 minutes). The wastewater was derived from the wastewater Laboratory of Polyester Industrial in Bogor. The results were analyzed, comprised of COD with Ferrous Ammonium Sulphate (FAS) method, phenol using aminoantipirin method, and 1,1,2,2-tetrachloroethane with Gas Chromatography-Flame Ionization Detector (GC-FID) method. The result of study shown that the configuration of the Ozone/ UV/GAC with an initial concentration of phenol 58,00 mg/L, COD 72,00 mg/L and 1,1,2,2-tetrachloroethane 32,96 mg/L resulted in the percentage of eliminating phenol 57,76%, COD 66,67% and 1,1,2,2-tetrachloroethane 98,74% while the configuration of Ozone/GAC with an initial concentration of phenol 55,00 mg/L, COD 72,00 mg/L and 1,1,2,2-tetrachloroethane 37,70 mg/L resulted in percentage of eliminating phenol 50,91%, COD 55,56% and 1,1,2,2-tetrachloroethane 100%ABSTRAKProses penyisihan senyawa fenol, Chemical Oxygen Demand (COD) dan 1,1,2,2-tetrakloroetana menggunakan teknik ozonasi katalitik dengan katalis Granular Activated Carbon (GAC) yang dikombinasikan dengan emisi sinar Ultra Violet (UV) dilakukan dalam penelitian ini. Tujuan dari penelitian ini untuk memperoleh efektivitas aplikasi teknik ozonasi katalitik menggunakan sistem konfigurasi, yaitu: Ozon/GAC dan Ozon/UV/GAC dalam penyisihan limbah fenol, COD dan 1,1,2,2-tetrakloroetana dengan waktu sirkulasi (0, 15, 30, 45, 60, dan 120 menit). Limbah cair yang digunakan berasal dari limbah cair Laboratorium Industri Polyester di daerah Bogor. Analisis yang dilakukan meliputi analisis COD dengan metode Ferro Ammonium Sulfat (FAS), analisis Fenol dengan menggunakan metode aminoantipirin dan analisis 1,1,2,2-tetrakloroetana dengan metode Gas Chromatography-Flame Ionization Detector (GC-FID). Setelah dilakukan penelitian, diketahui bahwa konfigurasi Ozon/UV/GAC dengan konsentrasi awal fenol 58,00 mg/L, COD 72,00 mg/L dan 1,1,2,2-tetrakloroetana 32,96 mg/L menghasilkan persentase penyisihan senyawa fenol 57,76%, COD 66,67% dan 1,1,2,2-tetrakloroetana 98,74% sedangkan konfigurasi Ozon/GAC dengan konsentrasi awal fenol 55,00 mg/L, COD 72,00 mg/L dan 1,1,2,2-tetrakloroetana 37,70 mg/L menghasilkan persentase penyisihan senyawa fenol 50,91%, COD 55,56% dan 1,1,2,2-tetrakloroetana 100%.